혹서기 음용수의 온도가 산란계의 생산성, 호르몬농도 및 혈액성상에 미치는 영향 - 임천익; 최일복; 백이; 류경선; Chun Ik Lim; Il Bok Choi; Md Masud Rana; Yee Paek; Kyeong Seon Ryu (농업생명과학연구, 2019)
본 연구는 국내의 고온다습한 하절기에 산란계에 음용수 온도가 생산성, 호르몬 농도 및 혈액성상에 미치는 영향을 구명하고자 실행하였다. 52주령 하이라인 갈색종 산란계 432수를 3개 처리구와 8반복으로 반복당 18수씩 케이지 사육장(550 cm2/수)에 배치하였고, 처리구별로 14.5, 24.0 및 32.5℃의 음용 수를 4주간 급수하였다. 산란계의 생산성은 산란율과 난중을 매일 조사하여 계산하였고, 호르몬, 혈액 성상 및 계란품질은 사양실험 종료 후 채집하여 분석하였다. 본 연구결과 산란율과 1일 산란양은 14.5℃ 의 급수구에서 유의적으로 개선되었고(p<0.05), 사료섭취량과 난중은 14.5와 24.0℃ 급수구에서 32.5℃ 에 비하여 현저히 증가하였다(p<0.05). 계란의 난백높이와 호우유닛은 음용수 온도에 따른 처리구간 통계적 차이가 없었다. 난각강도는 14.5℃ 급수 처리구에서 증가하였고(p<0.05) 난각두께도 개선되는 경향을 보였지만 처리구간에 통계적 차이는 없었다. 또한 혈청과 간의 GH와 IGF-I 농도는 32.5, 24.0 및 14.5℃ 급여구 순서로 증가하였고(p<0.05), 코티코스테론은 감소되었는데 14.5℃에서 가장 개선되었다(p<0.05). 이외에도 혈중 AST와 콜레스테롤은 14.5℃의 음용수 처리구에서 24.0과 32.5℃에 비하여 유의적으로 감소하였고(p<0.05), HDL콜레스테롤, 단백질 및 글루코오스는 처리구간에 통계적 차이가 없 었지만, 혈중 중성지방은 14.5℃처리구에서 현저하게 감소되었다(p<0.05). 그러므로 여름철 14.5℃의 음용수를 급여하면 산란계에서 고온스트레스를 저감하므로서 생산성, 계란품질 및 혈액성상을 개선하였다. An experiment was undertaken to investigate the effects of different drinking water temperature on performance, hormone concentration and blood composition of laying hens during hot-humid summer season (33℃ and 60%). A total of four hundred thirty two, fifty three age Hy-Line brown laying hens was used, divided into three treatments of eight replicates of twelve hens each (550 cm2/bird) until the end of the experiment fifty seven weeks. Treatments have consisted on at the set water temperature of 14.5, 24.0 and 32.5℃. Productive performances were evaluated by measuring egg production, egg weight, feed consumption, egg mass and feed conversion of eggs. At the end of trial, egg quality traits were measured, and the physiological performance determined by measuring some biochemical traits of blood and hormone concentration. Results of this study showed that egg production and daily egg mass were significantly (p<0.05) higher in 14.5℃ water treatment group but feed intake and egg weight did not differ statistically in between 14.5 and 24.0℃. Albumen height and haugh unit in eggs had not been affected by drinking different water temperature, while there was significant (p<0.05) increase of shell strength in 14.5 and 24.0℃ water temperature treatment group than 32.0℃ and shell thickness also was numerically increased in 14.5℃ without significance. Moreover, concentration of GH and IGF-I both serum and liver had significant (p<0.05) increase in the order of 32.5, 24.0 and 14.5℃ group, and serum corticosterone was significantly (p<0.05) decreased in drinking water of 14.5℃ treatment. Furthermore, serum AST and cholesterol were significantly (p<0.05) reduced in hens drunk 14.5℃ water compared with 24.0 and 32.5℃ water. HDL cholesterol, protein and glucose were not influenced by following water temperature, whereas lowest (p<0.05) natural fat was found in subject to 14.5℃ water treatment group. It could be concluded that during summer season especially under hot-humid period 14.5℃ drinking water temperature can improve the performance, egg quality and blood.